Exploring the impact of packaging interactions on quality of life among older consumers. Issue 3 (12th February 2016) - Ford, Nicholas; Trott, Paul; Simms, Christopher
ABSTRACT: This paper explores the concept of consumer vulnerability in the context of older consumers' packaging interactions. Consumer vulnerability is viewed as a situational state of powerlessness where marketplace imbalances or harm may occur from consuming marketing messages and/or products. The paper draws upon evidence from a series of in-depth interviews and observations with a cross section of 11 consumers aged between 59 and 85 years concerning their experiences with fast-moving consumer goods packaging. The findings reveal that changes as a result of the multiple dimensions of ageing can increase older consumers' risk of experiencing vulnerability during packaging interactions. The paper provides new insights to aid firms in empowering older consumers through packaging development, thus reducing vulnerability.